A Semantic Connection between the Word Cowardice and the other Vocabularies which Have the Same Meaning in " Lisan Al-Arab" Lexicon - Mustafa, Idrees Sulaiman (Journal of Tikrit University for Humanities, 2020)
The issue of semantic fields is a fertile place for study especially when the research connects with a study in Arabic lexicon . We have chosen to study the words which mean "cowardice" in "Lisan Al-Arab" lexicon because it is an original reference in linguistic research and a main lexicon in dealing with words language. Our research was based on finding semantic connection between the meaning of "cowardice" and words mentioned by Ibn Mandhor (711 A.H.) in his lexicon and their significances on the meaning that he mentioned. The words were divided into groups to be studied in the context because each word refers to the idea of cowardice from a different prospect.